Simulation Approach of End Milling Process Based on Finite Element Method - ZULKIFLI, MUHAMMAD NUR ARIFF; ABDULLAH, HASLINA (Research Progress in Mechanical and Manufacturing Engineering, 2022)
During end milling operation, the cutting tool pushes against the material, but the material is immovable. Some of that force cuts the material, but some of it pushes against the cantilevered cutting part. This pushing causes the tool to bend away from the centerline, and deflection of the tool occurred. These deflections also cause dimensions errors or surface errors on the completed component. This study presents a simulation of a three-dimensional cutting tool in end milling process using finite element analysis. This study aims to develop a simulation procedure using Abaqus software to determine the deflection and stress in a cutting tool of the milling process. The deflection value is determined based on the value stress, strain, and displacement obtained from the simulation. The simulation results indicate that the simulation-based on Finite element analysis can predict the stress and tool deflection.